An islamic perspective of the creation of universe - Al'Mahdi, Muhammad, Dr. (Kuala Lumpur : Saba Islamic Media, 2004)
This CD contains an explanation of Allah's creation of the physical universe through the various steps unfolding according to the Will of Allah all the way up to Adam, and through Adam to us today.
Host: Dr. Muhammad Al'Mahdi
Keywords: Islam; Creation -- Cosmology -- Cosmogony